Phase Transitions in Natural Vanadinite at High Pressures - Yingxin Liu (MDPI AG, 2021)
The structural stability of vanadinite, Pb5[VO4]3Cl, is reported by high-pressure experiments using synchrotron radiation X-ray diffraction (XRD) and Raman spectroscopy. XRD experiments were performed up to 44.6 GPa and 700 K using an externally-heated diamond anvil cell (EHDAC), and Raman spectroscopy measurements were performed up to 26.8 GPa at room temperature. XRD experiments revealed a reversible phase transition of vanadinite at 23 GPa and 600 K, which is accompanied by a discontinuous volume reduction and color change of the mineral from transparent to reddish during compression. The high-pressure Raman spectra of vanadinite show apparent changes between 18.0 and 22.8 GPa and finally become amorphous at 26.8 GPa, suggesting structural transitions of this mineral upon compression. The structural changes can be distinguished by the emergence of a new vibrational mode that can be attributed to the distortion of [VO4] and the larger distortion of the V–O bonds, respectively. The [VO4] internal modes in vanadinite give isothermal mode Grüneisen parameters varying from 0.149 to 0.286, yielding an average VO4 internal mode Grüneisen parameters of 0.202.